Employment and wage adjustments in Euroland's labour market: A bird's eye view - Helmut Hofer; Karl Pichelmann (Institute for Advanced Studies (IHS), 1999)
The paper attempts to establish a few stylised facts about Euroland's labour market given the increasing importance of smoothly functioning markets in the EMU. We assemble econometric evidence regarding labour demand behaviour, wage-setting mechanisms and the cyclicality of unemployment in Euroland. We find that in the 1990s unemployment cyclicality has been higher in Euroland than in the US, while the opposite was true in the previous two decades. The main reason for this is to be found in Euroland's employment now responding much stronger to cyclical fluctuations in output than in the past, and even somewhat stronger than in the US. Thus, it appears rather implausible that overall too strict employment protection regulations can still offer a convincing explanation for a significant part of Euroland's problem of persistently high unemployment. There can be little doubt, however, that wage-bargaining in Euroland continues to suffer from a serious insider-outsider problem.
Keywords: E24; J30; J64; 330; unemployment; wage-setting mechanisms; European Monetary Union